Respiratory Disease and its Management - McLuckie, A.; SpringerLink (Online service) (London : Springer London, 2009)
Recent advances in training for Intensive Care Medicine (ICM) have led to the introduction of competency based training, with a strong focus on the development of specific competencies at basic, intermediate and advanced stages of learning. This ensures trainees hold the appropriate skills and knowledge to undertake safe clinical practice, and thus provide good patient care. Respiratory Disease and its Management covers key topics, specific to the area of respiratory disease, that are addressed in the ICM training module. Issues range from conditions and illnesses such as asthma and pneumonia to treatments including ventilatory support and Inspired and Expired Gas Monitoring. Written by recognised experts in their subject area, and edited by Angela McLuckie, FRCA FJFICM Lead Clinician and Consultant Intensivist at Guy$1 (Bs and St Thomas$1 (BNHS Trust, London, UK, this book provides the reader with a compendium of knowledge and information. This book will be of special interest to critical care trainees, and will also appeal to nursing, pharmacy and physiotherapy staff.s
Acute Lung Injury and Acute Respiratory Distress Syndrome (ALI/ARDS) -- Life-Threatening Asthma -- Chronic Obstructive Airways Disease -- Diffuse Interstitial Lung Disease -- Pneumonia -- Pleural Effusions in the Critically Ill -- Pneumothorax in the Critically Ill -- Diagnosis and Management of the Obstructed Airway -- Postoperative Management of Patients Undergoing Lung Resection, Oesophagectomy or Thymectomy -- Indications for Ventilatory Support in Adults -- Modes of Invasive and Non-invasive Ventilatory Support -- Blood Gas Measurement and Interpretation -- Inspired and Expired Gas Monitoring -- Managing Secretions in the Ventilated Patient: The Role of Humidification, Suction, Physiotherapy, Mucolytics and Airway Adjuncts -- Drugs Acting on the Respiratory System -- Bronchoscopy in the Intensive Care Unit -- Tracheostomy and Mini-Tracheostomy -- Weaning from Mechanical Ventilation.
Keywords: Medicine; Radiology; Critical care medicine; Respiratory organs -- Diseases; Surgery; Medicine & Public Health; Pneumology/Respiratory System; Intensive / Critical Care Medicine; Imaging / Radiology; Surgery; Electronic books